Electromechanical Characterization and Locomotion Control of IPMC BioMicroRobot - Martin J.-D. Otis (Advances in Materials Science and Engineering)
This paper presents the electromechanical characterization of Nafion-Pt microlegs for the development of an insect-like hexapod BioMicroRobot (BMR). BMR microlegs are built using quasi-cylindrical Nafion-Pt ionomeric polymer-metal composite (IPMC), which has 2.5 degrees of freedom. The specific manufacturing process using a laser excimer for one leg in three-dimensional configurations is discussed. Dynamic behavior and microleg characteristics have been measured in deionized water using a laser vibrometer. The use of the laser vibrometer shows the linear characteristics between the duty cycle of square wave input and displacement rate of the actuator at multiple frequencies. This linearity is used to design a servo-system in order to reproduce insect tripod walking. As well, BMR current consumption is an important parameter evaluated for each leg. Current passing throughout the IPMC membrane can result in water electrolysis. Four methods are explained for avoiding electrolysis. The hardware test bench for measurements is presented. The purpose of this design is to control a BMR for biomedical goals such as implantation into a human body. Experimental results for the proposed propulsion system are conclusive for this type of bioinspired BMR.